2015
DOI: 10.1080/00071668.2014.988123
|View full text |Cite
|
Sign up to set email alerts
|

Juniper oil improves oxidative stability and eggshell and albumin quality of quail eggs

Abstract: 1. The aim of this study was to determine the effects of juniper oil (JO) dietary supplementation on the laying performance, egg traits and egg malondialdehyde (MDA) concentrations of quail. 2. A total of 400 female Pharaoh quails were equally divided into 4 groups containing 100 quails (5 replicates of 20 quails each). The study included a control treatment with no diet additives, and the treatments were as follows: (group 1) 100 mg JO/kg; (group 2) 200 mg JO/kg; (group 3) 300 mg JO/kg. The experiment was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…It may be contributed by the aforementioned antioxidative and antibacterial effects of phytoncides. In accordance with our observation, previous studies also demonstrated that dietary EOs improved egg Haugh units in laying hens (Abdel‐Wareth & Lohakare, ; Cengiz, Yesilbag, Meral, Cetin, & Biricik, ; Özek et al., ). Although exact mechanisms for its antioxidative property were not fully understood, a previous study by Kang et al.…”
Section: Discussionsupporting
confidence: 92%
“…It may be contributed by the aforementioned antioxidative and antibacterial effects of phytoncides. In accordance with our observation, previous studies also demonstrated that dietary EOs improved egg Haugh units in laying hens (Abdel‐Wareth & Lohakare, ; Cengiz, Yesilbag, Meral, Cetin, & Biricik, ; Özek et al., ). Although exact mechanisms for its antioxidative property were not fully understood, a previous study by Kang et al.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in performance response registered for quails from the WLS 25 group was assumed to occur due to the high level of cell wall compounds from the hulls, combined with the presence of non-starch polysaccharides in the kernel, being known for their negative influence on the digestion and absorption of nutrients from poultry feed [14,22]. Results similar to ours (egg intensity, feed consumption, FCR, egg weight) have been previously reported in the case of using standard compound feeds in the feeding of laying quails [69][70][71][72][75][76][77][78][79][80][81][82][83][84].…”
Section: Performance Responses Of Quailssupporting
confidence: 81%
“…However, Rutkowski et al [68] showed that an amount of up to 250 g/kg of whole yellow lupine seeds in the diets of laying hens did not produce significant changes in the final body weight of birds, compared with the group without lupine. Other studies presented body weight values for laying Japanese quails ranging between 211.5 and 371.1 g [69][70][71][72], an interval where the quail weights from the present research are situated.…”
Section: Performance Responses Of Quailsmentioning
confidence: 73%
“…Studies have demonstrated the chemical compositions of oils acquired from different parts (such as leaves and burls) of the juniper (Adams, ; Hernandez, Martinez, & Villanova, ; Milos & Radonic, ). Its components have been reported to have effects on the intestinal microbiota (Chaves, He, et al, ), growth performance (Yesilbag, Cengiz, Cetin, Meral, & Biricik, ) and egg and meat quality (Cengiz, Yesilbag, Meral, Cetin, & Biricik, ) in farm animals.…”
Section: Introductionmentioning
confidence: 99%